PENDIDIKAN KARAKTER KEPEMIMPINAN ANAK USIA 10-12 TAHUN BERBASIS PERMAINAN TRADISIONAL - Ferdinand, Rio; Nugrahanta, Gregorius Ari (Universitas Negeri Medan, 2023)
Character education is a topic that has received a lot of attention in order to develop the character potential of the nation's young generation. The research was conducted with the aim of developing a traditional game guidebook to improve the leadership character of children aged 10 to 12 years, determine the quality of the guidebook developed, and determine the effect of implementing the guidebook developed. The type of research used is Research and Development type ADDIE (Analyze, Design, Develop, Implement and Evaluate). The results of this research are a manual for traditional games to improve the leadership character of children aged 10-12 years which was developed using the ADDIE steps. The manual for traditional games to improve children's leadership character has a quality of